EVALUATION OF CYTOKINE IL-6 PROFILE IN PATIENTS HOSPITALIZED WITH COVID-19 IN THE 15TH REGIONAL HEALTH OF PARANA - Barroso Pelegrini, Brenda; Ferreira Evangelista, Fernanda; Aparecido Lacerda de Andrade, Felipe; Nishi, Letícia; Maria Colli, Cristiane; Costa Ferreira, Willian; de Laet Santana, Priscilla (Arquivos do Mudi, 2023)
COVID-19 is a viral infection caused by SARS-CoV-2 coronavirus, discovered in Wuhan, China, in 2019. It is a potentially serious disease with high transmissibility, characterized by worsening due to the exacerbated immune response, coordinated from pro-inflammatory cytokines signaling, leading to tissue damage. Objective: to evaluate the immunological profile of patients affected by COVID-19 through protein measurement that modulates immune response and has a great influence on cytokine storms. Materials and methods: the serum concentration analysis of the cytokine IL-6 was performed in patients with the disease. This procedure was developed through the duplicate capture ELISA technique, following manufacturer's standards, with the serum used from University Hospital of Maringa (HUM) patients who were hospitalized in the ward (G2), and who were in the intensive care unit but died (G3), as well as negative samples for COVID-19 (G1-control) from blood donors stored in the Maringa Regional Blood Center. Data were analyzed using GraphPad Prism software, version 7.0. Results: an increase in IL-6 was observed in more severe patients (G3). Conclusion: the cytokine IL-6 has been shown to be important prognostic markers of worsening of COVID-19.